2006
DOI: 10.1016/j.jpedsurg.2005.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Pepsin in bronchoalveolar lavage fluid: a specific and sensitive method of diagnosing gastro-oesophageal reflux–related pulmonary aspiration

Abstract: This study suggests that GOR-related aspiration plays a role in chronic cough in children with known GOR. Detecting pepsin in BAL fluid may therefore become an important adjunct in patient selection for antireflux surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
98
1
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(107 citation statements)
references
References 11 publications
3
98
1
5
Order By: Relevance
“…Additional modifications of our laboratory procedures to detect lower levels of amylase are warranted; however, the values we obtained were similar to those reported for patients receiving mechanical ventilation who had risk factors for aspiration and infections. 5,7,8 Our findings are consistent with those of other reports 5,6,[8][9][10][11][12]14,[26][27][28][29][30][31][32][33][34][35][36] of pepsin and amylase as biomarkers of microaspiration. Dewavrin and colleagues 36 argue that the use of amylase is only moderately accurate in diagnosing microaspiration.…”
Section: Discussionsupporting
confidence: 92%
“…Additional modifications of our laboratory procedures to detect lower levels of amylase are warranted; however, the values we obtained were similar to those reported for patients receiving mechanical ventilation who had risk factors for aspiration and infections. 5,7,8 Our findings are consistent with those of other reports 5,6,[8][9][10][11][12]14,[26][27][28][29][30][31][32][33][34][35][36] of pepsin and amylase as biomarkers of microaspiration. Dewavrin and colleagues 36 argue that the use of amylase is only moderately accurate in diagnosing microaspiration.…”
Section: Discussionsupporting
confidence: 92%
“…5 Thus, the detection of the above substances in BAL has been considered overall as a strong confirmation of gastric contents coming up from the stomach into the airways. Ozdemir et al 1 stated that BAL pepsin levels have been studied very poorly to diagnose gastroesophageal reflux (GERD) in patients with respiratory symptoms and quote the only investigation by Decalmer et al, 6 in which the authors found in controls lower levels of pepsin than those detected in chronic cough patients.…”
Section: 4mentioning
confidence: 99%
“…Interestingly, the highly specific and sensitive method for diagnosing GER -associated with respiratory tract aspiration is measurement of pepsin level in BAL. Since the gold-standard for diagnosis of microaspiration remains undetected, so the assessment of pepsin and bile salt presence to the gastrointestinal tract makes this diagnostic technique incredibly attractive [13]. In general, adjusting the response of fibrogenesis after the injury is used mainly for recent treatment in IPF, not on prevention of injury itself.…”
Section: Introductionmentioning
confidence: 99%
“…Bronchoscopy was done with patients in a semi recumbent position through the nasal route. Oxygen supply was given and oxygen saturation monitored by oximetry [13]. Instillations of at least 100 ml of sterile saline were done in a sub-segment of the right middle lobe or lingual for performing BAL.…”
mentioning
confidence: 99%